3D reflection seismic investigation for mine planning and exploration in the Kevitsa Ni-Cu-PGE deposit, Northern Finland - Malehmir, A.; Juhlin, C.; Wijns, C.; Urosevic, Milovan; Valasti, P.; Koivisto, E.; Kukkonen, I.; Heikkinen, P.; Paananen, M. (SEG, 2011)
A 3D reflection seismic survey was conducted over an area of about 9 km2 at the Kevitsa Ni-Cu-PGE (platinum group elements) deposit, Northern Finland. The principal objective of the survey was to image major fault and fracture zones at depth. Understanding the geometry of these zones is important for designing a steep open-pit for mining. Initial processing results suggest that the 3D seismic survey has been successful in imaging both gently dipping and steeply dipping reflections as shallow as 50 ms (or about 150 m), many of which correlate with fault systems and lithological contacts observed at the surface. Several new target areas can be identified in the seismic data that require further investigations for their mineralization potential.